Pastoral systems and agro-tourism in marginal areas of central Italy - Pardini A.; Longhi F.; Natali F. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
Despite the important environmental value of mountains, the low productivity of the land and the distance from the main roads cause migration of rural populations to towns, on a global scale. The subsequent land abandonment results in further degradation of the natural resources. In Tuscany (Central Italy), pasture abandonment is present above all in mountain areas, and this is due to difficult environmental conditions (hot dry summers, cold winters, shallow soils, rough topography) and difficult social conditions (distance to the main roads, distance to services and social life). The conventional agronomic techniques can help to overcome the low productivity level caused by the climate and the soil, nonetheless they cannot increase income sufficiently so as to fix people in the rural areas. Several agronomic actions have been taken to limit these negative trends, however, rural people often do not perceive the effectiveness of these interventions and seek further rise of their incomes and improvements of their lifestyle. A new approach consists in developing links between pastoralism and agriculture and the modern economy, especially agrotourism. A survey has been conducted to investigate the number and distribution of agrotourism initiatives in Tuscany, and interviews have been made to study the needs of the communities. The results suggest maintaining agricultural techniques and, above all, further integration of the conventional agro-pastoralism and services offered in rural areas.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)